Studi Interaksi Senyawa Turunan 1,3-Dibenzoiltiourea sebagai Ribonukleotida Reduktase Inhibitor - Lestari, Tresna (Jurnal Farmasi Indonesia, 2015)
In this research, docking process was carried out from 1,3-dibenzoylthio- urea derivates compound to ribonucleotide reductase receptor. The receptor used was 2EUD with ligand GCQ (Gemsitabine Diphosphate) obtained from the website of protein data bank (PDB). The purpose of this research was to ô°ind out the inter- action and toxicity of 1,3-dibenzoylthiourea derivates compound to ribonucleotide reductase receptor. All compounds was docked using ArgusLab 4.0.1 applications. The docking process performed by the method of ArgusDock. The validation of dock- ing used RMSD value gained < 2 that is 1, 704524 on calculate size X=16.5, Y=17.25 and Z=16.75. The analysis of docking result showed that 1,3-bis[(3-methylphenyl) carbonyl]thiourea compound can be predicted to have lowest free binding energy (Î?G) than comparative ligand and parent compound. From this research result can conclude that 1,3-bis[(3-methylphenyl)carbonyl]thiourea to inhibitor activity of ri- bonucleotide reductase receptor. Toxicity test accomplished using ToxTree applica- tion, with parameter such as Cramer Rules, Benigni / Bossa rulebase and Kroes TTC decision tree. Â Key word: Docking, 1,3-dibenzoylthiourea, ribonucleotide reductase inhibitor, toxicity